Quantitative comparison of the mRNA content of human iPSC‐derived motor neurons and their extracellular vesicles. Issue 2 (2nd February 2021) - Otake, Kentaro; Adachi‐Tominari, Keiko; Nagai, Hiroaki; Saito, Masayo; Sano, Osamu; Hirozane, Yoshihiko; Iwata, Hidehisa
Abstract : Extracellular vesicles (EVs) contain various cargo molecules, including RNAs and proteins. EVs, which include exosomes, are predicted to be suitable surrogates of their source cells for liquid biopsy to measure biomarkers. Several studies have performed qualitative comparisons of cargo molecule repertoires between source cells and their EVs. However, quantitative comparisons have not been reported so far. Furthermore, many studies analyzed microRNAs or proteins in EVs, but not mRNAs. In this study, we analyzed mRNAs in motor neurons and their EVs. Normal human‐induced pluripotent stem cells were differentiated into motor neurons, and comprehensive analysis of mRNAs in the cells and their EVs was performed by RNA sequencing. Differential analysis between cellular and EV mRNAs was performed by edgeR after normalization of read count. The results suggest that signatures in the abundance of EV mRNAs were different from those of cellular mRNAs. Comparison of intracellular vesicle and EV mRNA abundance showed negatively and positively biased genes in the EVs. Gene Ontology analysis revealed that the genes showing negatively biased abundance in the EVs were enriched in many functions regarding neuronal development. In contrast, the positively biased genes were enriched in functions regarding cellular metabolism and protein synthesis. These results suggest that mRNAs in motor neurons are loaded into EVs to regulate certain mechanisms, which are yet to be elucidated. Abstract : Extracellular vesicles (EVs) are secreted from various cell types and carry cargo derived from their source cells. However, the quantitative relationship between the cargos of EVs and that of their source cells is unclear, especially for mRNA. To elucidate this, we compared comprehensive RNA expression profiles using induced pluripotent stem cell‐derived motor neurons and their secreted EVs.